Pediatric Systemic Lupus Erythematosus and Lupus Nephritis Successfully Treated with Rituximab: A Case Series - Swetalina Pradhan; Gaurav Dash (Wolters Kluwer Medknow Publications, 2024)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease affecting multiple organ systems and skin with unpredictable flare and remission. Pediatric SLE is associated with significant morbidity and mortality due to severe organ involvement as compared to adults. Hence, management is challenging due to limited safe therapeutic options. Although systemic corticosteroids have been standard therapy, they have side effects such as infections, steroid-induced side effects, and organ toxicities and they delay skeletal growth in children. Hence, there is still a need for safe alternative drugs with good efficacy with sustained remission with minimal side effects, especially in children. Rituximab (RTX) has less adverse effects in comparison to systemic steroids which is a frequently prescribed drug in lupus nephritis (LN) for variable duration and also better tolerated among pediatric populations. However, it has conflicting results in terms of efficacy across different studies on adult and pediatric SLE. We are reporting a case series of pediatric SLE with LN treated successfully with 500 mg to 1 g RTX 15 days apart with significant improvement in skin lesions and LN without any recurrence and adverse reaction on long-term follow-up.